Maintenance treatment for opioid dependence with slow‐release oral morphine: a randomized cross‐over, non‐inferiority study versus methadone. (19th January 2014) - Beck, Thilo; Haasen, Christian; Verthein, Uwe; Walcher, Stephan; Schuler, Christoph; Backmund, Markus; Ruckes, Christian; Reimer, Jens
Abstract Aims To compare the efficacy of slow‐release oral morphine (SROM) and methadone as maintenance medication for opioid dependence in patients previously treated with methadone. Design Prospective, multiple‐dose, open label, randomized, non‐inferiority, cross‐over study over two 11‐week periods. Methadone treatment was switched to SROM with flexible dosing and vice versa according to period and sequence of treatment. Setting Fourteen out‐patient addiction treatment centres in Switzerland and Germany. Participants Adults with opioid dependence in methadone maintenance programmes (dose ≥50 mg/day) for ≥26 weeks. Measurements The efficacy end‐point was the proportion of heroin‐positive urine samples per patient and period of treatment. Each week, two urine samples were collected, randomly selected and analysed for 6‐monoacetyl‐morphine and 6‐acetylcodeine. Non‐inferiority was concluded if the two‐sided 95% confidence interval (CI) in the difference of proportions of positive urine samples was below the predefined boundary of 10%. Findings One hundred and fifty‐seven patients fulfilled criteria to form the per protocol population. The proportion of heroin‐positive urine samples under SROM treatment (0.20) was non‐inferior to the proportion under methadone treatment (0.15) (least‐squares mean difference 0.05; 95% CI = 0.02, 0.08; P > 0.01). The 95% CI fell within the 10% non‐inferiority margin, confirming the non‐inferiority of SROM to methadone. A dose‐dependent effect was shown for SROM (i.e. decreasing proportions of heroin‐positive urine samples with increasing SROM doses). Retention in treatment showed no significant differences between treatments (period 1/period 2: SROM: 88.7%/82.1%, methadone: 91.1%/88.0%; period 1: P = 0.50, period 2: P = 0.19). Overall, safety outcomes were similar between the two groups. Conclusions Slow‐release oral morphine appears to be at least as effective as methadone in treating people with opioid use disorder.